Biomechanical insights into differences between the mid-acceleration and maximum velocity phases of sprinting - Yu, J.; Sun, Y.; Yang, C.; Wang, D.; Yin, K.; Herzog, W.; Liu, Y. (The Journal of Strength and Conditioning Research, 2016)
Investigating the differences between distinct phases of sprint running may increase the knowledge about the specific physical abilities needed for different phases of sprinting. Differences between the mid-acceleration and maximum velocity phases of sprint running have not yet been adequately investigated. Twenty male sprinters performed maximum-effort sprint runs, and measurements were made at 12 m from start for the mid-acceleration phase and at 40 m from the start for the maximum velocity phase. Kinematic data and ground reaction forces (GRFs) were collected at a rate of 200 and 1000 Hz, respectively. Intersegmental dynamics analysis was performed to investigate the interaction of muscle torque (MUS) with other passive torques. The peak horizontal braking force was significantly lower for the acceleration compared with that for the maximal velocity phase, whereas the peak horizontal propulsive force was similar for both phases. The peak MUS at the hip and knee joints for the braking phase was significantly smaller in the acceleration phase than in the maximum velocity phase. In conclusion, compared with the maximum velocity phase, the lower horizontal braking force was the primary cause for the increase in running velocity during the mid-acceleration phase. The force produced by lower limb muscles required to counteract external torques caused by the horizontal braking force in the braking phase was smaller during the acceleration phase than the maximum velocity phase. Therefore, training aimed at reducing the horizontal braking force might be more important than increasing the force produced by the lower limb muscles for success of the mid-acceleration phase.